Dinámicas espaciales urbanas en las áreas de cesión de la ciudad de Palmira a escala barrial (2024)
The research topic focuses on the study of urban spatial dynamics and its influence on the formulation of guidelines for intervention in areas of cession in the city of Palmira with a special emphasis on effective public space.